A chromosome‐scale draft sequence of the Canada fleabane genome. Issue 6 (13th February 2020) - Laforest, Martin; Martin, Sara L; Bisaillon, Katherine; Soufiane, Brahim; Meloche, Sydney; Page, Eric
Abstract: Background: Due to the accessibility of underlying technologies the 'Omics', in particular genomics, are becoming commonplace in several fields of research, including the study of agricultural pests. The weed community is starting to embrace these approaches; genome sequences have been made available in the past years, with several other sequencing projects underway, as promoted by the International Weed Genome Consortium. Chromosome‐scale sequences are essential to fully exploit the power of genetics and genomics. Results: We report such an assembly for Conyza canadensis, an important agricultural weed. Third‐generation sequencing technology was used to create a genome assembly of 426 megabases, of which nine chromosome‐scale scaffolds cover more than 98% of the entire assembled sequence. As this weed was the first to be identified with glyphosate resistance, and since we do not have a firm handle on the genetic mechanisms responsible for several herbicide resistances in the species, the genome sequence was annotated with genes known to be associated with herbicide resistance. A high number of ABC‐type transporters, cytochrome P450 and glycosyltransferases (159, 352 and 181, respectively) were identified among the list of ab initio predicted genes. Conclusion: As C. canadensis has a small genome that is syntenic with other Asteraceaes, has a short life cycle and is relatively easy to cross, it has the potential to become a model weed species and, with the chromosome‐scale genome sequence, contribute to a paradigm shift in the way non‐target site resistance is studied. © 2020 Her Majesty the Queen in Right of CanadaPest Management Science © 2020 Society of Chemical Industry Abstract : The chromosome‐scale genome sequence of the economically important weed Conyza Canadensis is presented. This data will facilitate the study of weedy traits such as herbicide resistance with genetic tools. © 2020 Her Majesty the Queen in Right of CanadaPest Management Science © 2020 Society of Chemical Industry